ENHANCEMENT OF INTEGRATIVE LANGUAGE TEACHING BASED ON AI TECHNOLOGIES AND STATISTICAL EVALUATION OF RESULTS (Центральноазиатский журнал образования и инноваций, 2025)
this article explores the enhancement of integrative language teaching through the application of artificial intelligence technologies. It presents the results of experimental studies conducted among medical students learning English and Latin. The study analyzes how AI tools contribute to the improvement of language skills, motivation, and academic performance. A statistical evaluation of the outcomes demonstrates the effectiveness of AI-based methods in multilingual education. The findings support the integration of AI into language curricula to achieve more personalized and adaptive learning environments.